Local Level Disaster Response Effectiveness in Nepal: Recent (31 March) Tornado as a Case Study - S B Malla; R K Dahal; S Hasegawa (International Association of Lowland Technology, 2020)
Nepal is amongst the most disaster-prone countries in the world.Annually more than 400 people are dying in various naturaldisasters. More than 80% of the population is at risk from naturalhazards like a landslide, flood, fire, cold wave, wind storm,avalanche, inundation, and glacial lake outburst.Surprisingly on 31st March 2019, a Tornado occurred inParsa and Bara districts. It was for the first time in the history ofNepal that a tornado of such magnitude occurred and causedsuch devastations. Twenty-eight people lost their lives and morethan 600 got severely injured. More than 1400 houses wereturned into rubble.In the immediate aftermath response operations werelaunched. Security forces including government agencies andhumanitarian organizations made their efforts to render rescueand relief to the victims. But the response effort was notsufficient. Keeping this tornado response as a case study thispaper examines the gap prevalent in local level disasterresponse mechanism in Nepal.During the research, it was found that the capacity of civilservants, bureaucrats, and elected representatives functioning atthe local level is not enough to render an effective response.